Surgical management of giant Xp11.2 translocation renal cell carcinoma with multivisceral invasion: a case report of en bloc resection and targeted-immunotherapy success - Luo, Bohan; Luo, Han (Frontiers in Oncology, 2026)
A 36-year-old man presented with a 1-month history of abdominal distension and a 3-day palpable mass. Imaging demonstrated a 20-cm left renal tumor with adjacent organ infiltration and suspicious lymphadenopathy, radiologically suggestive of sarcoma or advanced malignancy. He underwent radical en bloc resection including left nephrectomy, distal pancreatectomy, splenectomy, and partial colectomy due to tumor invasion of the pancreatic tail, splenic vessels, and descending colon mesentery. Histopathology confirmed Xp11.2 translocation/TFE3 gene fusion renal cell carcinoma. Surveillance MRI at 3 months postoperatively revealed local recurrence, prompting combination therapy with sunitinib (VEGF inhibitor) and sintilimab (anti-PD-1 antibody). Follow-up imaging demonstrated significant regression at 1 month, with no evidence of disease progression at 12-month reassessment.